O papel dos municípios na regulação jurídica da expansão urbana na zona costeira: limites e possibilidades - Almeida, Guadalupe Maria Jungers Abib de (2013)
The Brazilian Constitution of 1988 and the Statute of the City have improved the development and urban expansion policies establishment, but only the issue of the Federal Law No. 12.608, of April 10, 2012, introduced standards directly related to the process of urban expansion and the role of municipalities in the respective legal regulation. The current legal landscape has important consequences in the Brazilian municipalities located in the coastal zone. In the last decades these regions, especially the northern coast of São Paulo State, have subjected to land use conflicts and economic pressures that led to a chaotic urbanization. Indeed, the region still facing geographical, environmental and legal barriers when considering the processes of urban expansion planning, as it comprises areas especially protected by federal and state legislation (the Brazilian National System of Conservation Units, State Park Serra do Mar and the Atlantic Forest Law), as well as it undergoes the Coastal Ecological Economic Zoning, established by the Union and by Member State. The present work was conduced by employing an integrated approach which considers the legal standards related to coastal zone, derived from the legislative powers exerted by the different instances and their reflexes in the municipalities competences for the regulation of legal policy towards urban expansion, also linked with data and correlated aspects of the North Coast of São Paulo State. By adopting the referred method, we approached the following aspects: a) From the analysis of the possible conflicts arising from the application of regulatory rules issued by the Union and the Member State, overlapping or opposing the municipal master plan, we proposed some measures to ensure legal federal cooperation and minimize these potential incompatibilities; b) by analyzing the standards and guidelines of the Brazilian Constitution of 1988 and of the City Statute, in particular the legal rules introduced by Federal Law No. 12.608/2012, we exposed the minimum content required by municipal urban expansion policies, as well as outlined the role of the master plan and traced the outlines of the legislative competence for the municipalities